Photobioanodes Based on Nanoimprinted Electrodes and Immobilized Chloroplasts. Issue 2 (19th November 2021) - Aleksejeva, Olga; Nilsson, Nicklas; Genevskiy, Vladislav; Thulin, Kristian; Shleev, Sergey
Abstract: As the global energy demand continues to increase, the interest in photosynthetic energy conversion is growing accordingly. Chloroplasts, photosynthetic organelles present in plants and algae, are attractive candidates for construction of bio solar cells; however, they have been less studied because of their complex membrane system, which restricts electrochemical communication with an electrode surface. Nevertheless, in this work photobioanodes based on planar and nanoimprinted gold substrates modified with chloroplasts were designed and evaluated. Apparently, nanoimprint lithography contributed to higher photocurrent densities, not only owing to the enlarged real surface area, but also due to boosting electrochemical communication between the photosynthetic organelles and the electrode. Combining chloroplast‐modified nanoimprinted gold electrodes with a capacitive part made of a planar gold substrate, coated with a conductive polymer, resulted in a dual‐feature photobioanode providing a lower open‐circuit potential, i. e ., −0.11 V vs . Ag|AgCl|KClsat, and an enhanced capacitance of ca . 37 F m −2 upon illumination of 400 W m −2 . Abstract : A low potential, highly capacitive dual‐feature anode, composed of nanostructured (using nanoimprint lithography – an industry‐scale throughput, cost‐effective and versatile method) gold electrodes modified with chloroplasts and poly(3, 4‐ethylenedioxythiophene), was designed and evaluated.